In situ preparation and characterization of biocompatible acrylate‐terminated polyurethane containing chemically modified multiwalled carbon nanotube. (19th May 2017) - Alishiri, M.; Shojaei, A.
Abstract : Biodegradable acrylate‐terminated polyurethane/acrylate (APUA) filled with 2‐hydroxyethyl methacrylate functionalized carbon nanotube (CNT‐HEMA) was prepared by in situ free radical crosslinking. CNT‐HEMA enhanced crystallinity of soft domain and caused more phase separation between hard and soft domains of APUA. Tensile testing showed a considerable improvement in elastic modulus (∼160%) and tensile strength (∼30%) at 1 wt% loading. Morphological features of APUA induced by nanotubes were found to be dominant on mechanical properties of APUA/CNT‐HEMA. CNT‐HEMA increased water contact angle of APUA; however, wettability of APUA/CNT‐HEMA maintained in acceptable range for biomedical applications. APUA/CNT‐HEMA exhibited lower hydrophobic nature compared to many CNT filled polyurethanes reported in literature due to HEMA functional group, making APUA/CNT‐HEMA nanocomposites adequate for biomedical applications. POLYM. COMPOS., 39:E297–E307, 2018. © 2017 Society of Plastics Engineers